Answer

Verified

408.3k+ views

Hint: Since we have three equations here, we will take one equation and express it in terms of any other equation and try to solve it.

Complete step-by-step answer:

The equation given to us are

${x^2} - 4{y^2} + {z^2} = 37$----------(i)

$xz=24$---------(ii)

$ \Rightarrow z = \dfrac{{24}}{x}$

$x+2y-z=11$------(iii)

Now, let us consider eq (iii)

x+2y-z=11

This, can be written as

x-z=11-2y

Now, let us square both the sides so that we can express this in terms of eq(i)

So, we get ${(x - z)^2} = {(11 - 2y)^2}$

${x^2} + {z^2} - 2xz = 121 + 4{y^2} - 44y$

${x^2} + {z^2} - 4{y^2} - 2xz = 121 - 44y$

But, already from eq(i), we had ${x^2} - 4{y^2} + {z^2} = 37$

So, let us substitute this value here

So, we get

37-2(24)=121-44y

-44y=-132

From this, we get y=3

To get the value of x , let us substitute this value of y in eq(iii),

So, we get

x+2y-z=11

x+2(3)-z=11

x+6-z=11

From eq (ii), we get $z = \dfrac{{24}}{x}$

So, substituting this value in the above equation ,we get

$x - \dfrac{{24}}{x} = 5$

On solving this further, we get

$

{x^2} - 24 = 5x \\

\Rightarrow {x^2} - 5x - 24 = 0 \\

$

On factorising this, we get

$

{x^2} - 3x + 8x - 24 = 0 \\

\Rightarrow x(x - 3) + 8(x - 3) = 0 \\

\Rightarrow x = 3, - 8 \\

$

Putting these values of x in $z = \dfrac{{24}}{x}$, we get

In the first case, let us consider the value of x=3,so z=$\dfrac{{24}}{3} = 8$

In the second case, let us consider the value of x=-8, so we get z=$\dfrac{{24}}{{ - 8}} = - 3$

So, z=8,-3

So, from this , we can write x=-8,3 ; y=3; z=-3,8

So, option B is the correct answer for this question.

Note: In these type of questions, first try to manipulate a specific equation and try to express in terms of another equation which is given in the data so that we can easily find out the required values(in this case x,y,z) using those equations.

Complete step-by-step answer:

The equation given to us are

${x^2} - 4{y^2} + {z^2} = 37$----------(i)

$xz=24$---------(ii)

$ \Rightarrow z = \dfrac{{24}}{x}$

$x+2y-z=11$------(iii)

Now, let us consider eq (iii)

x+2y-z=11

This, can be written as

x-z=11-2y

Now, let us square both the sides so that we can express this in terms of eq(i)

So, we get ${(x - z)^2} = {(11 - 2y)^2}$

${x^2} + {z^2} - 2xz = 121 + 4{y^2} - 44y$

${x^2} + {z^2} - 4{y^2} - 2xz = 121 - 44y$

But, already from eq(i), we had ${x^2} - 4{y^2} + {z^2} = 37$

So, let us substitute this value here

So, we get

37-2(24)=121-44y

-44y=-132

From this, we get y=3

To get the value of x , let us substitute this value of y in eq(iii),

So, we get

x+2y-z=11

x+2(3)-z=11

x+6-z=11

From eq (ii), we get $z = \dfrac{{24}}{x}$

So, substituting this value in the above equation ,we get

$x - \dfrac{{24}}{x} = 5$

On solving this further, we get

$

{x^2} - 24 = 5x \\

\Rightarrow {x^2} - 5x - 24 = 0 \\

$

On factorising this, we get

$

{x^2} - 3x + 8x - 24 = 0 \\

\Rightarrow x(x - 3) + 8(x - 3) = 0 \\

\Rightarrow x = 3, - 8 \\

$

Putting these values of x in $z = \dfrac{{24}}{x}$, we get

In the first case, let us consider the value of x=3,so z=$\dfrac{{24}}{3} = 8$

In the second case, let us consider the value of x=-8, so we get z=$\dfrac{{24}}{{ - 8}} = - 3$

So, z=8,-3

So, from this , we can write x=-8,3 ; y=3; z=-3,8

So, option B is the correct answer for this question.

Note: In these type of questions, first try to manipulate a specific equation and try to express in terms of another equation which is given in the data so that we can easily find out the required values(in this case x,y,z) using those equations.

Recently Updated Pages

Three beakers labelled as A B and C each containing 25 mL of water were taken A small amount of NaOH anhydrous CuSO4 and NaCl were added to the beakers A B and C respectively It was observed that there was an increase in the temperature of the solutions contained in beakers A and B whereas in case of beaker C the temperature of the solution falls Which one of the following statements isarecorrect i In beakers A and B exothermic process has occurred ii In beakers A and B endothermic process has occurred iii In beaker C exothermic process has occurred iv In beaker C endothermic process has occurred

The branch of science which deals with nature and natural class 10 physics CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Define absolute refractive index of a medium

Find out what do the algal bloom and redtides sign class 10 biology CBSE

Prove that the function fleft x right xn is continuous class 12 maths CBSE

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Give 10 examples of unisexual and bisexual flowers

What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.

Draw a diagram of nephron and explain its structur class 11 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

State the laws of reflection of light

Difference Between Plant Cell and Animal Cell

Change the following sentences into negative and interrogative class 10 english CBSE